HUBUNGAN USIA IBU DENGAN LAMA PELEPASAN PLASENTA PADA KALA III PERSALINAN DI PRAKTIK MANDIRI BIDAN YULIS AKTRIANI,S.Tr,Keb: bahasa indonesia - Aisyah, Lestari Nur; Yuliani, Ita; Yulifah, Rita (Jurnal Pendidikan Kesehatan (e-Journal), 2023)
The Maternal Mortality Rate in Indonesia is still the highest in Southeast Asia and is still far from the global target of the Sustainable Development Goals. One of the highest contributors to death is bleeding during childbirth. Stage III is a stage of labor that has a relatively short duration, can endanger the mother's life because of the increased risk of bleeding and lead to maternal death. This study aims to determine the relationship between maternal age and the duration of placental separation in the third stage of labor. This research method uses a correlational study research design with a retrospective approach. The sample of this study was 138 mothers who met the inclusion criteria. Using a purposive sampling technique. The data collection method used secondary data from medical records and partograph sheets, then the data were analyzed using Chi Square. The results of this study were almost all 77.5 percent of the mother's age were 20 until 35 years old, while almost all of the time 82.6 percent of the placenta was detached was not long. Statistical test chi square obtained a value of p more than 0.05 that H0 is rejected, meaning that there is a relationship between maternal age and the incidence of prolonged placental detachment in the third stage with an OR of 5.7, the maternal age at risk will cause the incidence of prolonged placental detachment 5 , 7 times more than the age of mothers who are not at risk. It is hoped that mothers, especially mothers who are at risk of age, understand the importance of planning for childbirth so as to prevent complications during delivery, especially the problem of the length of time the placenta is released.